Respostas
respondido por:
0
x⁴ -7x² +12=0. => -7/12= -3-4/-3•-4
(x² -3) . (x² -4) = 0
x²=3 . x²=4
x=±√3 x= ±2
respondido por:
3
Resposta:
Explicação passo-a-passo:
Determine , no conjunto R, o conjunto solução da seguinte equação biquadrada:
Para ser biquadrada:
x^4 - 7x² + 12=0
(X^2)^2 - 7x^2 + 12 = 0
X^2 = y
y^2 - 7y + 12 = 0
a = 1; b = - 7; c = 12
/\= b^2 - 4ac
/\ = (-7)^2 - 4.1.12
/\ = 49 - 48
/\ = 1
Y = [- b +/- \/ /\] / 2a
Y = [- (-7) +/- \/1] / 2.1
Y = [ 7+/- 1]/2
Y' = [7+1]/2 = 8/2 = 4
Y" = [7-1]/2 = 6/2 = 3
X^2 = y
X^2 = 4
X = \/4
X = +/- 2
X^2 = y
X^2 = 3
X = +/- \/3
R.: v = [+\/3 ; - \/3; 2; - 2]
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás